2017
DOI: 10.1186/s12885-016-3016-4
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib versus sunitinib as first-line treatment agents in Chinese patients with metastatic renal cell carcinoma: the largest multicenter retrospective analysis of survival and prognostic factors

Abstract: BackgroundTo compare the efficacy of sorafenib and sunitinib with regard to overall survival (OS) and progression free survival (PFS) in Chinese patients with metastatic renal cell carcinoma (mRCC).MethodsA multicenter, retrospective study was performed to elucidate the relationship between clinical variables and prognosis comparing sorafenib and sunitinib as first-line treatment agents in Chinese patients with mRCC. Between September 2006 and December 2014, 845 patients received either sorafenib (400 mg bid; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…Certain ethnic groups are also poorly represented in RCTs. Our analysis included several RWD studies in Asian populations that were of particular interest [43,45,[48][49][50]. Studies conducted in Asian populations reported 7.8-11.0 months mPFS, 16.5-33.2 months mOS, and 21-33% ORR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain ethnic groups are also poorly represented in RCTs. Our analysis included several RWD studies in Asian populations that were of particular interest [43,45,[48][49][50]. Studies conducted in Asian populations reported 7.8-11.0 months mPFS, 16.5-33.2 months mOS, and 21-33% ORR.…”
Section: Discussionmentioning
confidence: 99%
“…RWD studies used a variety of sources to extract data, including national and local cancer registries, insurance databases, pharmacy databases, and patient medical records [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Studies were from a wide range of countries, including USA, Canada, Australia, Spain, France, Greece, Italy, Netherlands, Czech Republic, China, Japan, Korea, and India.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Single agent TKI treatment remains important in China where pembrolizumab+axitinib and nivolumab+ipilimumab are not available. Differences have been reported in the efficacy and safety seen with TKIs in Chinese patients compared to Western patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In AXIS study, all the patients enrolled were treated with sunitinib previously, while in our study, sorafenib was used as first-line therapy in 45% (19/42) of the patients. In the western population, sunitinib showed better efficacy than sorafenib in the first-line treatment, while in the eastern population, the advantage seemed to be not obvious (32)(33)(34). Cabozantinib is another multi-kinase inhibitor and also showed prominent efficacy in the second-line treatment.…”
Section: Discussionmentioning
confidence: 99%